Implikasi Hukum Terhadap Pembatalan Rencana Perkawinan Setelah Proses Mappetuada Dalam Adat Bugis Makassar - Ruslan, Dyah Auliah Rachma (PATTIMURA Legal Journal, 2023)
Introduction: In the marriage process of the Makassar Bugis community, it is not uncommon for one of the parties to cancel the marriage plan after the mapettuada/proposal procession. This is of course a polemic in itself because in the mapettuada process there is a certain amount of money and goods that have been handed over from the prospective groom (money panai') to the prospective bride. In this research, the researcher will discuss the legal implications of canceling marriage plans after the mappettuada procession in Bugis Makassar custom. Purposes of the Research: Provide an explanation regarding the legal implications of canceling marriage plans after the mappettuada procession in Makassar Bugis custom. Methods of the Research: Methods of the Research is normative legal research. The sources of legal materi als used are primary and secondary legal materials. The technique for collecting legal materials used in this research is through literature study, all materials obtained will be analyzed qualitatively and then presented prescriptively. Results Originality of the Research: Cancellation of marriage plans after the mappetuada process in Bugis Makassar custom requires the party canceling the marriage to bear the loss of costs incurred by the other party as regulated in the provisions of Article 1365 of the Civil Code.